Relation of fetal and infant growth to plasma fibrinogen and factor VII concentrations in adult life. Issue 6820 (18th January 1992) - Barker, D. J.; Meade, T. W.; Fall, C. H.; Lee, A.; Osmond, C.; Phipps, K.; Stirling, Y.
Abstract : OBJECTIVE--To determine whether reduced fetal and infant growth are associated with higher plasma fibrinogen and factor VII concentrations in adult life. DESIGN--Follow up study of men born during 1920-30 whose weights at birth and at 1 year had been recorded by health visitors, and men born during 1935-43 whose size at birth had been measured in detail. SETTING--Hertfordshire and Preston, England. SUBJECTS--591 men born in east Hertfordshire who still lived there and 148 men born in Preston who still lived in or close to the city. MAIN OUTCOME MEASURES--Plasma fibrinogen and factor VII concentrations. RESULTS--Among men in Hertfordshire mean plasma fibrinogen and factor VII concentrations fell with increasing weight at 1 year (from 3.21 g/l in men of less than or equal to 18 lb to 2.93 g/l in men greater than or equal to 27 lb and from 122% of standard to 103%; p less than 0.001, p less than 0.005 respectively). The trends were independent of cigarette smoking, alcohol consumption, body mass index, and social class. Neither plasma fibrinogen nor factor VII concentration was related to birth weight. In men in Preston, however, fibrinogen concentration fell progressively as the ratio of placental weight to birth weight decreased (p = 0.01). CONCLUSIONS--Reduced growth in fetal life and infancy is strongly related to high plasma concentrations of the haemostatic factors fibrinogen and factor VII. This may be a persisting response to impaired liver development during a critical early period.